Társadalmi különbségek a magyarországi gyerekek fogainak állapotában és egészségmagatartásában - Tamás Hajdu; Gábor Kertesi; Petra Fadgyas-Freyler (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
– Our study examines social inequalities in dental visits, the status of primary and permanent teeth, the dental treatments, the availability of publicly funded dental care and health behaviours related to dental health among Hungarian children. We use all available administrative and survey data sources to provide a comprehensive picture. We show that there are already significant social differences in dental health, dental visits and health behaviours at the age of 2-3 years, which are compounded by significant social gaps in access to publicly funded dental care. These early childhood gaps often widen with age. We conclude our study with health and social policy implications that can help reduce social disparities in children's dental health.
Keywords: I10; I12; I14; J13; 330; social inequality; dental health; health behaviour; childhood